Identification of FDFT1 as a potential biomarker associated with ferroptosis in ccRCC. (24th March 2022) - Huang, Ruizhen; Zhang, Chiyu; Wang, Xing; Zou, Xin; Xiang, Zhengjie; Wang, Zewei; Gui, Bin; Lin, Tao; Hu, Honglin
Abstract: Renal cell carcinoma (RCC) seriously threatens people's lives and health. The identification of some precise biomarkers during the process of RCC progression and the pathophysiologic procedure is critical for improving the diagnosis and management of RCC. Evidence suggests that ferroptosis may play a pivotal role in eradicating clear cell RCC (ccRCC, KIRC) tumor cells. We screened out the target prognostic ferroptosis‐associated genes and examined the functions of farnesyl‐diphosphate farnesyltransferase (FDFT1) in 786‐O cells by plasmid transfection. In our study, we identified FDFT1 as a potential marker correlating with ferroptosis in KIRC. Upregulated FDFT1 inhibited cell proliferation, migration, and invasion, and the underlying antitumor effects may occur via the AKT signaling pathway. Our study provides helpful evidence to study the complex physiopathology of KIRC. Abstract : By regulating the farnesyl‐diphosphate farnesyltransferase (FDFT1) expression, GPX4 expression, iron, and malondialdehyde levels were significantly changed, FDFT1 inhibited KIRC cell proliferation, migration, and invasion may be associated with ferroptosis.